Ageing masculinities in contemporary European and Anglophone cinema
1 online resource (xiii, 237 pages)
Keywords: "This volume offers a unique exploration of how ageing masculinities are represented in contemporary international cinema. With chapters spanning a range of national cinemas, the primarily European focus of the book is juxtaposed with analysis of the social and cultural constructions of manhood and the 'anti-ageing' impulses of male stardom in contemporary Hollywood. These themes are inflected in different ways throughout the volume, from considering how old age is not the monolithic and unified life stage it is often framed as, to exploring issues of queerness, sexuality, and asexuality, as well as themes such as national cinema and dementia. Offering a diverse and multifaceted portrait of ageing and masculinity in contemporary cinema, this book will be of interest to scholars and students of film and screen studies, gender and masculinity studies, and cultural gerontology about a variety of national cinemas"--